Machining characteristics of Al/Ticp/Gr hybrid composites. (2018) - Sozhamannan, C.G.; Naveenkumar, K.; Mathiarasu, A.; Velmurugan, K.; Venkatachalapathy, V.S.K.
Abstract: In recent years, Hybrid composite materials replacing traditional composite materials because of it's provided excellent wear resistant, mechanical properties and improved machinability. Hybrid composite materials are very difficult to machine since the presence of multiple reinforcement in the matrix. The Al/TiCp/Gr hybrid composite is fabricated by stir casting route. The machining characteristics were analyzed by turning process with varying depth of cut and feed rate. The tool wear examined by using scanning electron microscope. The surface roughness was analyzed by surface tester. The experimental results revealed that tool wear and surface roughness mainly influenced by cutting process parameters.